Peningkatan Kemampuan Pra Braille Melalui Penggunaan Media Papan Pantule Bagi Siswa Tunanetra Kelas I di SLB Bhakti Luhur Baumata Kupang - Eko, Yohana; Selan, Ot Bil Wilson; Wangge, Vinsensius (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This classroom action research aimed to improve the pre-Braille skills of two first-grade visually impaired students at SLB Bhakti Luhur Baumata Kupang through the use of a